The relation of coaching context and coach education to coaching efficacy and perceived leadership behaviors in youth sport - Sullivan, P.; Paquette, K. J.; Holt, N. L.; Bloom, G. A. (The Sport Psychologist, 2012)
The purposes of this study were to examine how coaching context and level of coaching education were related to coaching efficacy and, subsequently, how coaching efficacy was related to perceived leadership behaviors in youth sports. One hundred and seventy-two youth sport coaches completed the Coaching Efficacy Scale and Revised Leadership Scale for Sports. Structural equation modeling revealed that coach education significantly affected the multidimensional construct of coaching efficacy whereas coaching context did not. Coaching efficacy predicted perceived leadership behaviors comprising training and instruction, positive feedback, social support, and situational consideration. These findings question the issue of coaching efficacy as a factor that may distinguish between coaches at different organizational contexts but highlight the importance of coach education training for improving coaching efficacy in youth sport.